2010
DOI: 10.1016/j.virol.2010.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-mediated neutralization of Ebola virus can occur by two distinct mechanisms

Abstract: Human Ebola virus (EBOV) causes severe hemorrhagic fever disease with high mortality and there is no vaccine or treatment. Antibodies in survivors occur early, are sustained, and can delay infection when transferred into nonhuman primates. Monoclonal antibodies (mAbs) from survivors exhibit potent neutralizing activity in vitro and are protective in rodents. To better understand targets and mechanisms of neutralization, we investigated a panel of mAbs shown previously to react with the envelope glycoprotein (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 59 publications
6
65
0
Order By: Relevance
“…Several MAbs to EBOV GP, for example, KZ52, ZGP133/3.16, and JP3K11, were shown to neutralize EBOV effectively in vitro by inhibiting the cellular entry pathway of the virus (16,17,33,37,38). In contrast, there has been no report demonstrating an effective neutralizing MAb against MARV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several MAbs to EBOV GP, for example, KZ52, ZGP133/3.16, and JP3K11, were shown to neutralize EBOV effectively in vitro by inhibiting the cellular entry pathway of the virus (16,17,33,37,38). In contrast, there has been no report demonstrating an effective neutralizing MAb against MARV.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that focused on the interaction between EBOV GP and neutralizing monoclonal antibodies (MAbs) indicated that the direct inhibition of GP attachment to its ligand(s)/ receptor(s) or the fusion of viral and host cell membranes is likely to be a key mechanism of neutralization (17,33,38). Our most recent study demonstrated that passive immunization with wellcharacterized neutralizing MAbs had beneficial effects in a nonhuman primate model of Ebola hemorrhagic fever (21), highlighting the potential of antibody therapy against filovirus infection.…”
mentioning
confidence: 99%
“…In the absence of reverse genetics systems and/or biosafety level 4 (BSL-4) facilities required for work with filoviruses, researchers use various surrogate systems for characterization of filovirus-specific MAbs or investigation of various steps of filovirus life cycle involving GP. These systems include chimeric vesicular stomatitis Indiana viruses (VSV) with the G protein replaced with filovirus GP (19)(20)(21) and pseudotyped gammaretroviruses (22,23) and lentiviruses (24)(25)(26), which have their respective envelope proteins replaced with a filovirus GP provided in trans. It is generally assumed that these surrogate systems can be used to accurately characterize neutralizing properties of filovirus polyclonal or monoclonal antibodies.…”
mentioning
confidence: 99%
“…We considered whether the poorer protection from EBOV challenge in macaques given the combination vaccines as compared to only the EBOV vaccine might relate to a skewing of the response toward or against the GP mucin domains. Although correlates of protective immunity with regard to responses to the mucin domain are poorly defined, it has been shown that removal of the mucin domain reveals additional neutralizing epitopes 36,37 and that antibodies to the mucin domain can be protective in mice. 38 Of interest, the genome sequences reported for the EBOV strain causing the recent epidemic of Ebola hemorrhagic fever in West Africa were reported to be~97% homologous with earlier strains from the Democratic Republic of Congo and Gabon.…”
Section: Discussionmentioning
confidence: 99%